Enhancing Mathematical Connection Ability through Scratch-Assisted Problem-Based Learning: A Mixed-Methods Study in Exponent Topics - Annisa, Nurul Fadilah; Sudihartinih, Eyus; Usdiyana, Dian; Luneta, Kakoma (FKIP Universitas Lampung, 2025)
This study aims to investigate the role of Scratch multimedia in enhancing junior high school students' mathematical connection skills related to the topic of exponents. This study employed a mixed-methods design, integrating quantitative and qualitative approaches, with 25 ninth-grade students as participants. Six students were purposively selected for in-depth interviews. Quantitative data were collected through pre-tests and post-tests and analyzed using paired-samples t-tests. In contrast, qualitative data were obtained from observation and interview results, and were analyzed thematically to identify the main themes during the learning process. Quantitatively, the study's results showed a significant increase in each indicator of mathematical connection skills. The indicator of connections between mathematical ideas (M post-test = 78.40, M pre-test = 45.20, t(24) = 7.43, p = 0.002) with an N-Gain value of 61% showed a fairly good increase. The connection indicator between mathematical representations (M post-test = 93.32, M pre-test = 58.40, t(24) = 4.89, p < 0.001) with an N-Gain value of 84% demonstrated a significant improvement. The connection indicator of mathematics with real-life problems (M post-test = 74.40, M pre-test = 24.20, t(24) = 6.18, p < 0.001) showed a significant improvement, with an N-Gain value of 61%, indicating a strong connection. Qualitatively, the study's results revealed three main themes: the use of Scratch multimedia in exponential learning enhances students' understanding of the material, creates a fun learning experience, and strengthens understanding through games. This study shows a positive impact of Scratch multimedia on improving students' mathematical connection abilities. Future research can utilize longitudinal studies to determine whether learning improvements are sustained in the long term. Keywords: mathematical connection, mathematics learning, scratch multimedia.